Effectiveness of Mediation and Arbitration in Indonesian Construction Contract Disputes - Dahris Siregar (jfpublisher, 2026)
In Indonesia's building industry, default issues happen all the time. Going to court to settle them can take a long time, cost a lot of money, and hurt business ties. The point of this study is to look into how well Mediation and Arbitration work as an alternative way to settle building contract failures. A legal-normative, qualitative study method was used to look at legal provisions (Construction Services Law, Arbitration Law) and conflict settlement practices at national arbitration institutions (BANI) as well as mediation practices in Indonesia. The study's results show that these two processes are very helpful. Mediation is an open and mutually agreeable way to settle a dispute, with the goal of keeping the parties' relationship. Arbitration, on the other hand, gives a clear and final decision more quickly, and is made by a judge with experience in the building field. The main result is that arbitration and mediation work better and faster than going to court. The research adds to the body of knowledge in the field of construction law about Alternative Dispute Resolution (APS). It also helps contracting parties choose the best dispute resolution clause and promotes the use of APS to keep construction projects on track and ensure they don't stop.